1992
DOI: 10.1177/004051759206201109
|View full text |Cite
|
Sign up to set email alerts
|

Yarn Hairiness and the Process of Winding

Abstract: The influence of winding on yam hairiness is examined, and increased hairiness during winding is verified using a Zweiglc hairiness tester. Spccifically, this study concentrates on the increase of wild hairs on the yam surface after winding, and the relationship between winding tension and yarn hairiness. Fiber transfer is proposed to explain the increased wild hairs; experimental results verify that fiber transfer occurs. A theory is proposed to explain the mechanism of fiber transfer during winding, and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Hair length distribution is well documented in the literature [14,16,17,22,23,26]; It has been shown to have an exponential or an almost-exponential pattern. Barella and Manich [17,26] fitted two (in some cases three) exponential segments to the hair length distribution of various yarn types.…”
Section: Protruding Hair Length Distribution -Zweigle Hairiness Testermentioning
confidence: 97%
See 1 more Smart Citation
“…Hair length distribution is well documented in the literature [14,16,17,22,23,26]; It has been shown to have an exponential or an almost-exponential pattern. Barella and Manich [17,26] fitted two (in some cases three) exponential segments to the hair length distribution of various yarn types.…”
Section: Protruding Hair Length Distribution -Zweigle Hairiness Testermentioning
confidence: 97%
“…Hairiness of staple yarns is due to the protrusion of fiber ends and loops from the yarn core [13][14][15]. Its critical importance as a measure of yarn surface integrity has been extensively documented in the literature.…”
Section: Yarn Hairinessmentioning
confidence: 99%
“…Rust and Peykamian [21] revealed that fibers migrate even during the winding process, increasing yam hairiness afterwards, and a higher winding tension and/or higher yam velocity leads to more fiber migration and hence more severe yarn hairiness. Tarafder [23] studied the influence of the winding process on yam hairiness; he observed that the increased hairiness at the bottom of the bobbin was greater than that at the top after winding.…”
mentioning
confidence: 99%